Influence of gate bias on the avalanche ruggedness of SiC power MOSFETs - Fayyaz, Asad; Castellazzi, Alberto; Romano, G.; Riccio, M.; Urresti, J.; Wright, N. (2017)
This paper investigates the effect of negative gate bias voltage (VGS) on the avalanche breakdown robustness of commercial state-of-the-art silicon carbide (SiC) power MOSFETs. The device’s ability to withstand energy dissipation during avalanche regime is a connoting figure of merit for all applications requiring load dumping and/or benefiting from snubber-less converter design. The superior material properties of SiC material means that SiC MOSFETs even at 1200V exhibit significant intrinsic avalanche robustness.